Characterisation of evolutionarily conserved key players affecting eukaryotic flagellar motility and fertility using a moss model. Issue 2 (13th April 2020) - Meyberg, Rabea; Perroud, Pierre‐François; Haas, Fabian B.; Schneider, Lucas; Heimerl, Thomas; Renzaglia, Karen S.; Rensing, Stefan A.
Summary: Defects in flagella/cilia are often associated with infertility and disease. Motile male gametes (sperm cells) are an ancestral eukaryotic trait that has been lost in several lineages like flowering plants. Here, we made use of a phenotypic male fertility difference between two moss ( Physcomitrella patens ) ecotypes to explore spermatozoid function. We compare genetic and epigenetic variation as well as expression profiles between the Gransden and Reute ecotype to identify a set of candidate genes associated with moss male infertility. We generated a loss‐of‐function mutant of a coiled‐coil domain containing 39 (ccdc39) gene that is part of the flagellar hydin network. Defects in mammal and algal homologues of this gene coincide with a loss of fertility, demonstrating the evolutionary conservation of flagellar function related to male fertility across kingdoms. The Ppccdc39 mutant resembles the Gransden phenotype in terms of male fertility. Potentially, several somatic (epi‐)mutations occurred during prolonged vegetative propagation of Gransden, causing regulatory differences of for example the homeodomain transcription factor BELL1. Probably these somatic changes are causative for the observed male fertility defect. We propose that moss spermatozoids might be employed as an easily accessible system to study male infertility of humans and animals in terms of flagellar structure and movement.